PERFORMANCE OF SOYBEAN ( YBEAN (GLYCINE MAX L.) UNDER ORGANIC PRODUCTION SYSTEM - S. B. YOGANANDA,; N. DEVKUMAR,; AND G. K. SHRUTHI, P. THIMME GOWDA (The Bioscan, 2018)
A field experiment was conducted during kharif seasons of 2013, 2014, 2015 and 2016 at Zonal Agricultural Research Station, V. C. Farm, Mandya to evaluate the performance of soybean (Glycine max L.) under organic production system. The experiment consists of eleven treatments replicated thrice in RCBD design. Among the various treatments, application of 100% N equivalent compost + recommended FYM (10 t/ha) + beejamrutha (seed treatment) + jeevamrutha (500 liter/ha) recorded significantly higher seed yield during all the years of experimentation (1174, 1173, 1258 and 1325 kg/ha, respectively) and also in their pooled data (1233 kg/ha). This increased yield was attributed to more availability of nitrogen (289.3 kg/ha), phosphorus (35.85 kg/ha) and potassium (185.6 kg/ha) in the soil compared to other treatments. Soil chemical properties, viz. soil pH, organic carbon content and electric conductivity, were not influenced by application of the organic manures. However, there was an improvement in the soil chemical properties compared to initial soil data.